Microstructural and electrical transport properties of uniaxially pressed Bi 1.65Pb 0.35Sr 2Ca 2.5Cu 3.5O 10 + δ ceramic superconductors - Cruz García, A. (2018)
We have studied the effect of the pelletization pressure on microstructural and electrical transport properties of superconducting ceramics with starting composition given by the formula Bi 1.65Pb 0.35Sr 2Ca 2.5Cu 3.5O 10 + δ. The experimental data of electrical measurements was processed in order to obtain the weak-link resistivity, the orientation probability of the grains’ a-axes along a certain preferential direction, the slope of the linear part in the temperature dependence of the ab-planes resistivity, and the intrinsic effective anisotropy of the grains, of each sample. In contrast with the behaviour of Bi 1.65Pb 0.35Sr 2Ca 2Cu 3O 10 + δ ceramics, the Ca, Cu enriched samples exhibit a reduction of their effective anisotropy at sample level and weak links resistivity with increasing compacting pressures. In addition, a compacting pressure of around 488 MPa may affect considerably the electrical and structural parameters of the material. The results suggest that a combined effect of the pelletization pressure and the doping with Ca and Cu can be used to improve the electrical transport properties of these materials for technological applications.